IMPROVING PAYAKUMBUH ELEMENTARY TEACHERS' ABILITY IN DESIGNING MATHEMATICAL HIGHER ORDER THINKING SKILLS PROBLEMS - Fridgo Tasman (Fakultas MIPA Universitas Negeri Padang, 2019)
The 2015 PISA (Program for international students assessment) results put Indonesia in 65th position out of 72 countries. The results show that the mathematical abilities of Indonesian students are still very low. These low abilities include. : (1) understanding complex information; (2) theory, analysis and problem solving; (3) use of tools, procedures and problem solving; and (4) conducting an investigation. These four abilities are known as high-order thinking skills (HOTS). Similar conditions are also found in the city of Payakumbuh. Based on interviews with several elementary school teachers from Payakumbuh it was revealed that students were not used to solving problems that demanded HOTS because in general teachers are also not trained to design mathematical problems with high cognitive levels. They tend to give questions at low level. As a result, this is not developing students' mathematical abilities. Based on this, a community partnership program was implemented with the aim of increasing the ability of elementary school teachers to design questions to assess HOTS. The activity partners were high school elementary school teachers in Groups 1 and 3 of Payakumbuh, which numbered 55 people. Activities are packaged in the form of a combination of workshops and implementation in schools. In the workshop, the teachers were given knowledge and skills in designing HOTS questions by the resource person. Next, the teachers in groups designed HOTS questions. The questions that have been designed by the teacher are validated together, then tested to students in grades IV, V, and VI. Based on the collected data, it is known that there was an increase in the ability of high-class teachers in Elementary Groups 1 and 3 of Payakumbuh in solving HOTS questions. The ability of the teachers to design HOTS questions also increased, although some of the questions that were designed were still slightly above the application (few still want high analysis, evaluating, or creating).